Union membership and employment dynamics: A note - Marcus Dittrich; Beate Schirwitz (Center for Economic Studies and ifo Institute (CESifo), 2010)
We analyze union behavior in a model with membership dynamics and compare the labor market outcomes to static union models. Based on empirical findings we modify standard models and show that the well-known result that static models overstate distortions caused by unions only holds in the special case of firm-level wage setting. If, however, the union is big enough to determine employment for the whole sector, it rather depends on both the elasticity of labor demand and union's time preference whether static frameworks overrate or even underrate unions' distortions.
Keywords: C61; J50; J51; 330; unions; endogenous membership; bargaining centralization; Gewerkschaftlicher Organisationsgrad; Lohnverhandlungstheorie; Tarifpolitik; Gewerkschaftspolitik; Mitgliedschaft; Theorie